Implementation of the Least Square Method in the Work Plan and Budget Application (SIREKA) at Politeknik Negeri Lhokseumawe - Rizqillah, Rizqillah; Arhami, Muhammad; Abdi, Musta’inul; Arifai, Muhammad; Meilvinasvita, Dwi (Politeknik Negeri Lhokseumawe, 2025)
Every year, all units at the Lhokseumawe State Polytechnic (PNL) are required to plan activity plans and budgets (RKA). This includes Library units, Departments, SPI, P3M, P4M, and other units. However, the process of planning activities to budget realization still depends on Drive services, causing complexity and lack of coordination in managing data. To overcome this problem, a solution is needed in the form of SIREKA (Work Plan and Budget Management Information System). In this application, the least squares method is used as a prediction tool for activity budget data. From the results of the calculations carried out, it is known that the least squares method has a high level of accuracy of 97.71% with a MAPE value of 2.29%, so this method is considered successful. The implementation of SIREKA has been successful in overcoming RKA obstacles in PNL, as well as providing budget predictions that are useful for decision making. SIREKA has proven itself to be a solution that has a positive impact on the Politeknik Negeri Lhokseumawe.